Denial, Media and Endurance in Infection Control in Kosova - Raka, Lul; Mulliqi, Gjyle; Dedushaj, Isuf; Krasniqi, Selvete; Gjergji, Tahire; Krasniqi, Avdyl; Salihu, Drita; Spahija, Gazmend (International Journal of Infection Control, 2009)
Nosocomial infections constitute an important public health problem in developing and transitional countries. Kosova is the poorest country in Europe and communicable diseases are a major health problem. The annual per capita government expenditure in health care is only 35 €. Infection control in Kosova is in its infancy. The main challenges in this field are the lack of financial support and political commitment, an inadequate number of trained personnel, overcrowded wards, poor management and technological gap. In the past, infection control was limited to passive monitoring. Nosocomial infections were denied or hidden by hospital administrators. The public and mass media have had a great impact on the initiation of governmental activities in the field of safety and quality in health care institutions. A turning point in the approach to infection control was pressure from the mass media after an MRSA outbreak in the ICU during December 2005. Government has institutionalized infection control through the National Committee for Prevention and Control of Nosocomial Infections. Although devoid of any funding, the committee is making small steps towards ensuring safer care in health care institutions. Future steps in infection control should ensure the sustainability of any initiated activities.